2016
DOI: 10.1080/10641955.2016.1239737
|View full text |Cite
|
Sign up to set email alerts
|

Increased circulating Th22 cells correlated with Th17 cells in patients with severe preeclampsia

Abstract: Increased circulating Th22 cells, which were correlated with Th17 cells, were observed in patients with sPE. The immune imbalance between T helper (Th) cells may contribute to the pathogenesis of sPE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 25 publications
4
25
0
Order By: Relevance
“…Of note, IL‐17A correlated with IL‐2 and IFN‐γ production, suggesting that T H 17 cells mediate their function by stimulating T H 1 cytokines . This was in agreement with the study of Zhang et al, which additionally indicated a positive linear correlation between T H 17 and T H 22 cells ( r = 0.461, P ‐value = 0.013). Interestingly, IL‐17 was found to be expressed not only in T H 17, but also in CD8 and NK cells of PE women .…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Of note, IL‐17A correlated with IL‐2 and IFN‐γ production, suggesting that T H 17 cells mediate their function by stimulating T H 1 cytokines . This was in agreement with the study of Zhang et al, which additionally indicated a positive linear correlation between T H 17 and T H 22 cells ( r = 0.461, P ‐value = 0.013). Interestingly, IL‐17 was found to be expressed not only in T H 17, but also in CD8 and NK cells of PE women .…”
Section: Resultssupporting
confidence: 90%
“…The maternal serum IL‐17 levels have been investigated by several observational studies, although resulting in conflicting results. Two case‐control studies, including 60 and 119 women, respectively, measured significantly higher third‐trimester IL‐17 levels in the PE group . This finding was confirmed by Cao et al, observing higher IL‐17 mRNA expression in peripheral blood mononuclear cells (PBMCs), as well as elevated IL‐17 serum levels, both in mild and severe PE.…”
Section: Resultsmentioning
confidence: 54%
“…These correlations go in hand with Zhang et al (24) who detected a positive correlation between plasma IL-22 concentration and the percentage of Th22 cells and severe PE patients and data obtained by Poordast et al (26) support the rational of imbalance of cytokine profile in PE patients.…”
mentioning
confidence: 52%
“…Also, Cornelius et al (23) experimentally found on transfer of Th17 cells resulting from reduced uterine perfusion in induced tissue oxidative stress, increased serum IL-6 and causes increased blood pressure and intrauterine growth restriction and concluded that autoimmune status associated with Th17 cells may have a role in pathogenesis of PE. Thereafter, Zhang et al (24) found plasma concentrations of IL-17 and IL-22 were significantly increased along with a decreased plasma IL-10 concentration in severe PE patients and Ribeiro et al (25) found plasma levels of IL-6, IL-17 and TNF-α were significantly higher whereas IL-10 levels were significantly lower in PE than in normotensive women. Also, Poordast et al…”
mentioning
confidence: 99%
“…On the other hand, Treg cells are considered to play a crucial role in the implantation of embryos and the maintenance of maternal immune tolerance to the fetus . Zhang et al . demonstrated that the percentage of Treg cells defined as CD4 + CD25 + CD127 low was significantly lower in women with severe PE compared with healthy pregnant women.…”
Section: Discussionmentioning
confidence: 99%